Chiloe, an Egalitarian Rural Society. Agricultural Income and Land Distribution After Independence - Robles-Ortiz, C; Navarrete-Montalvo, J; Llorca-Jana, M (UNIV MAGALLANES, 2018)
This article assesses both agricultural income distribution and land distribution in Chiloe during the 1830s-1850s, comparing both variables with the rest of the Chilean provinces at that time, in a rather unexplored period in Chile s agrarian historiography. We have used several untapped sources such as the Catastro ( agricultural census). From this source, we have built and processed an over half a million records database for the first three agricultural censuses of 1832, 1837 and 1852. Our results show a very egalitarian distribution of both agricultural income and land in Chiloe c. 1830-1855, an exceptionality within Chile. This uniqueness of Chiloe is mainly explained by policies applied from late colonial times, in particular the granting of land to creole and indigenous people, as well as by a process of land partition soon after independence, being both processes unique to Chile.